Églises doubles ou familles d'églises: les cinq églises du Hemmaberg (Mont Sainte-Hemma) - Glaser, Franz (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 1997)
Abstract The Hemmaberg is (with modern designation) a centre of worship, that has gained entry to the archaeological literature since the beginning of our century thanks to R. Egger's publication. Since that time a double church (with a baptistery) has been known (beginning of &''century). The resumption of excavations further resulted in an other church being the origin of the centre of worship (beginning of 5